Engaging Digital Natives in Digital Cultural Preservation - Robertus Ilabakho; Dumbiri, Rita (Knowledge Garden: International Journal of Library Studies, 2026)
Digital cultural preservation has become increasingly important in the era of Digital 4.0, where digital natives are the primary users and creators of digital technologies. Libraries and librarians play a strategic role in preserving cultural heritage while encouraging active public participation in preservation initiatives. This study aims to identify effective strategies for engaging digital natives in digital cultural preservation through library services. A qualitative research approach was employed using an extensive literature review and in-depth interviews with librarians and digital native participants involved in digital cultural preservation activities. The collected data were analyzed using thematic analysis to identify recurring patterns and key engagement strategies. The findings indicate that successful engagement depends on three major strategies: providing accessible and user-friendly digital cultural resources, adopting collaborative and participatory preservation practices that involve digital natives in content creation and curation, and implementing digital literacy and educational programs that enhance awareness of cultural heritage preservation. These strategies strengthen digital natives' appreciation of cultural heritage while increasing their participation in preservation activities. The study concludes that digital cultural preservation requires collaborative efforts between libraries, librarians, and digital natives supported by innovative digital technologies. It is recommended that libraries continuously develop interactive digital platforms and community-based preservation programs to ensure the long-term sustainability and accessibility of digital cultural heritage.